2019
DOI: 10.1158/1541-7786.mcr-18-1327
|View full text |Cite
|
Sign up to set email alerts
|

The Pluripotency Regulator PRDM14 Requires Hematopoietic Regulator CBFA2T3 to Initiate Leukemia in Mice

Abstract: PR domain-containing 14 (Prdm14) is a pluripotency regulator central to embryonic stem cell identity and primordial germ cell specification. Genomic regions containing PRDM14 are often amplified leading to misexpression in human cancer. Prdm14 expression in mouse hematopoietic stem cells (HSC) leads to progenitor cell expansion prior to the development of T-cell acute lymphoblastic leukemia (T-ALL), consistent with PRDM14's role in cancer initiation. Here, we demonstrate mechanistic insight into PRDM14-driven … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…More recently, in a derived inducible FLAG-PRDM14 mouse model, PRDM14-induced T-cell ALL was driven by activated Notch1 through a RAG-mediated deletion-based mechanism ( Figures 3E and 5) [194]. Furthermore, novel findings demonstrated that PRDM14 requires the master hematopoietic regulator CBFA2T3 to initiate leukemia in progenitor cells [195].…”
Section: Prdm14mentioning
confidence: 87%
“…More recently, in a derived inducible FLAG-PRDM14 mouse model, PRDM14-induced T-cell ALL was driven by activated Notch1 through a RAG-mediated deletion-based mechanism ( Figures 3E and 5) [194]. Furthermore, novel findings demonstrated that PRDM14 requires the master hematopoietic regulator CBFA2T3 to initiate leukemia in progenitor cells [195].…”
Section: Prdm14mentioning
confidence: 87%
“…In myeloid differentiation, CBFA2T3 interacts with PU1 to repress stem cell genes [ 22 ]. CBFA2T3 can also partner with PRDM14 on DNA and participates in T-ALL development [ 39 ]. Finally, in B-cell lineage, and in Diffuse Large B-cell Lymphoma in particular, CBFA2T3 is reported to be part of the LMO2 complex regulating kinetochore function, chromosome assembly, and mitosis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, mouse models of RUNX1 overexpression do not lead directly to cancer by itself but increases cancer predisposition [ 47 , 48 ]. CBFA2T3 is required to initiate Prdm14 -induced T-acute lymphoblastic leukemia, demonstrating its oncogenic role [ 39 ]. Even though we demonstrated here an interaction between CBFA2T3 and ETV6-RUNX1 proteins, we did not obtain any evidence that CBFA2T3 could act directly onto ETV6-RUNX1 function.…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence that protein-binding partners are critical for PRDM14's function, PRDM14's functional partners in a cancer model have only recently been described [40]. Interestingly, PRDM14's primary interacting partner in the T-ALL mouse model is CBFA2T3, a related family member to PRDM14's partner in PGCs, CBFA2T2.…”
Section: Prdm14 Requires Protein Binding Partners For Cancer Initiationmentioning
confidence: 99%
“…It is possible that the ETO fusion proteins elevate expression levels of a pluripotency factor such as PRDM14, triggering genome instability; alternatively, it is possible that PRDM14-driven tumours have genome instability due to mis-appropriation of the ETO/CBFA2T family members. It is difficult to separate the CBFA2T3 and PRDM14 functions in mouse leukemias, since mice lacking CBFA2T3 do not have expanded hematopoietic progenitor cells and do not develop leukemia when PRDM14 is mis-expressed [40]. Certainly, the association of CSCs with genetic events that take place in progenitor cells rather than more differentiated cells may be explained by the hijacking of resident proteins.…”
Section: Model Of Stem Cell Expansion and Increased Dna Damagementioning
confidence: 99%